Urgency of Ability Read The Qur'an Islamic Religious Education Students Class Of 2021 Faculty Of Tarbiyah and Teacher Sciences IAIN Kendari - Marzuki Marzuki; Sufiani Sufiani (Lambaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2023)
This study aims to determine the urgency of the ability to read the Qur’an for Islamic Religious Education student class of 2021 at the Faculty of Tarbiyah and Teacher Training IAIN Kendari. This type of research is a qualitative research using field research methods. Data collection techniques used were observation, interviews, and documentation with data analysis techniques, namely data reduction, data presentation, data collection verification. The techniques for testing the validity of the data use source triangulation techniques, technical triangulation and time triangulation. The results of the study show that the urgency of the ability to read the Qur’an for PAI students is two, namely: a) making PAI students as professional teacher candidates. b) become the main requirement for PAI students in completing their studies. There are three efforts made to foster the ability to read the Qur’an for PAI students, namely: a) conducting reading mapping for new students. b) conducting tahsin reading coaching for students. c) the establishment of an institution called the Student Qur'an House (RQM) as a forum/place for students to improve their ability to read the Qur'an. In addition, there are two supporting factors in guiding students to read the Al-Qur'an properly, namely: a) the existence of faculty policies. b) the establishment of an institution as a place for fostering Al-Qur'an reading.